SUPERCRITICAL-CO2 EXTRACTION OF SAPONINS FROM FURCRAEA SELLOA VAR. MARGINATA AND SPENT CAMELLIA SINENSIS OF GOLDEN APPLE SNAIL MITIGATION - RAMLI@YUSOF, NOOR HAFIZAH (2020)
Golden apple snail (Pomacea canaliculata) have become a major constraint to the profitability of rice (Oryza sativa L.) farming by damaging rice seedlings during early paddy growth. The use of synthetic chemical molluscicides such as Bayluscide which is based on niclosamide to control the snails is toxic to the environment and human health. The foaming property of saponins has the capability to eliminate the water snails. However, the use of conventional extraction to extract saponins exhibited low yield of active compounds. Green extraction method like supercritical fluid extraction has proven to give great benefit compared to the conventional methods such as higher extraction efficiency